Propuesta de un plan estratégico para la empresa ISABA S.A de la ciudad de Manta periodo 2021-2025 - Valdez Cusme, María Yaneth (2021)
The objective of this research was to develop a strategic plan in the company ISABA S.A in Manta city, period 2019-2023 for the improvement of administrative management; therefore, methods, techniques and tools were implemented that allowed us to know the internal and external factors of the construction company that helped to detect errors for the respective decision-making. To carry out the investigation, three phases were done; Phase I, the current situational diagnosis where real aspects were evaluated in ISABA SA, through EFI, SWOT matrices which effectively helped the performance of the construction company, an interview and a respective survey were also applied to them to know in depth the status of the construction. In phase II, strategies were formulated with the design of the matrix combined with the intention of eliminating its weaknesses, threats and optimizing its opportunities, which consisted in the creation of the mission, vision, values, objectives and policies, in the phase III, a strategic control was developed using the Deming circle to be able to solve each problem encountered and that the company constantly increase quality and be more effective and finally we have the realization of the proposal of the strategic plan that was carried out with the purpose to investigate possible strategies using the 5W + 1H tool. In conclusion, the purpose of the strategic plan proposal is to make it possible to achieve the objectives and, at the same time, make it a useful tool for decision-making.